Mark Meerovich Prize – QUATTUOR - Василий Лисицин (Проект Байкал)
The annual Mark Meerovich Prize is awarded in Irkutsk for the fourth time. The prize was founded in honour of the famous Soviet and Russian architectural historian and architect, Doctor of Historical Sciences and Doctor of Architecture, Professor, Honoured Architect of Russia Mark Grigorievich Meerovich (1956-2018). The article describes the award ceremony and provides information about the laureates of the year 2024: Elena Treskina and Ekaterina Matel.